Sublethal impacts of essential plant oils on biochemical and ecological parameters of the predatory mite Amblyseius swirskii - Ghasemzadeh, Somayyeh; Messelink, Gerben J.; Avila, Gonzalo A.; Zhang, Yongjun (Frontiers in Plant Science, 2022)
The generalist predatory mite Amblyseius swirskii is a widely used natural enemy of phytophagous pests. Due to negative effects of conventional pesticides on non-target organisms, the development of selective natural and eco-friendly pesticides, such as essential plant oils, are a useful pest control tool to use in synergy with biological control agents. Essential oils of Nepeta crispa, Satureja hortensis and Anethum graveolens showed promising results to control Tetranychus urticae. Hence an experiment was carried out to evaluate the effects of these essential oils on biochemical and demographic parameters of A. swirskii. A significant reduction of carbohydrate, lipid and protein contents of oil-treated predatory mites was observed. However, essential oils of S. hortensis and A. graveolens had no effect on lipid reserves. Glutathione-S-transferase activity of A. swirskii was influenced by A. graveolens oil treatment. In addition, the enzyme activity of the α-esterases was elevated by all treatments. The essential oils showed no effect on β-esterases activity compared to the control treatment. None of the concentrations of the different tested oils affected the population growth parameters of A. swirskii. However, a significant reduction was observed in oviposition time and total fecundity of predatory mites. A population projection predicted the efficacy of predatory mites will likely be decreased when expose to the essential oils; however, population growth in the S. hortensis treatment was faster than in the other two treatments not including the control. Results presented in this study may have critical implications for Integrated Pest Management (IPM) programs. However, our observations show that using the tested essential plant oils requires some caution when considered as alternatives to synthetic pesticides, and in combination with A. swirskii. Semi-field and field studies are still required to evaluate the effects on T. urticae and A. swirskii of the essential oils tested in this study, before incorporating them in IPM strategies.